2009
DOI: 10.1007/s11244-009-9357-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Incorporation Order of Pt- and Ba-Precursors on the Structure and Catalytic Performance of NSR Catalysts

Abstract: The structural properties and the performance of two NO X storage-reduction (NSR) catalysts prepared as a function of the deposition order of Pt-and Ba-precursors was investigated. The catalyst obtained by incorporating first Ba turned out to be more active mainly due to the larger regeneration extent achieved at temperatures below 350°C. This behaviour was related to the larger external Pt/Ba interface exhibited by this catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…4). No CO(g) nor 6 any carbonyl species could be observed at anytime at 300C, indicating that essentially all of 7 the CO introduced during the rich phased was converted. 8 In contrast, a large band of CO(g) (showing the P and R branches of the 9 rotovibrational spectrum) were observed both at 100 and 200C.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…4). No CO(g) nor 6 any carbonyl species could be observed at anytime at 300C, indicating that essentially all of 7 the CO introduced during the rich phased was converted. 8 In contrast, a large band of CO(g) (showing the P and R branches of the 9 rotovibrational spectrum) were observed both at 100 and 200C.…”
Section: Introductionmentioning
confidence: 98%
“…A description of the NSR technique 5 and a review of the activity of many materials have been reported elsewhere [3]. The 6 understanding of NSR technology has been hampered by the fact that various (usually non-7 realistic) reaction conditions were often used and a very large number of model materials with 8 varying formulations were investigated [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22]. 9 Several studies have been devoted to commercial NSR materials [23,24,25,26] and in 10 situ FTIR studies [27,28,29,30], but rarely the combination of the two has been reported.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations